2019
DOI: 10.3390/app9163392
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Photovoltaic Performance as a Function of Positioning Relative to the Focus Points of a Concentrator PV Module: Case Study

Abstract: This article examines the positioning features of polycrystalline, monocrystalline, and amorphous silicon modules relative to the focus points of concentrator photovoltaic modules under real meteorological conditions using a dual tracking system. The performance of the photovoltaic modules mounted on a dual-axis tracking system was regarded as a function of module orientation where the modules were moved step by step up to a point where their inclination differed by 30° compared to the ideal focus point positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…By investigating the relationships between tracking inaccuracy and performance in traditional PV technologies, Nsengiyumva et al (2018) [54] found that, regardless of the cardinal direction, an inaccuracy of 10 • in solar tracking caused a mere 1.5% decrease in performance. Contrary to that, however, a three-year-long series of measurements carried out in Hungary detected a more complex relationship [67]. In the latter research project, three different PV technologies (m-Si; p-Si; a-Si) were compared by means of a dual axis solar tracking mounting system.…”
Section: Azimuth-elevationmentioning
confidence: 97%
See 1 more Smart Citation
“…By investigating the relationships between tracking inaccuracy and performance in traditional PV technologies, Nsengiyumva et al (2018) [54] found that, regardless of the cardinal direction, an inaccuracy of 10 • in solar tracking caused a mere 1.5% decrease in performance. Contrary to that, however, a three-year-long series of measurements carried out in Hungary detected a more complex relationship [67]. In the latter research project, three different PV technologies (m-Si; p-Si; a-Si) were compared by means of a dual axis solar tracking mounting system.…”
Section: Azimuth-elevationmentioning
confidence: 97%
“…The insensitivity point of 3 • , determined by this study, may also have economic implications by highlighting the question, whether in the design of solar tracking devices the 3 • threshold should be surpassed, and if yes, to what extent. In addition, the research findings may be useful regarding the planning of solar tracking systems and the calculations of investment costs and returns in the case of m-Si, p-Si, and a-Si PV systems [67].…”
Section: Azimuth-elevationmentioning
confidence: 99%
“…For instance, if the target diverges from the rectilinear trajectory and performs maneuvers, α and β have to be chosen from a wide range of values in order to be sure that the tracking system ensures an accurate target tracking. However, if the deviation is due to the noise induced by the measurement to a greater extent than that caused by the maneuvers of the target, α and β must be chosen rather small to ensure that the tracking system is positioned correctly [35].…”
Section: α-β Tracking Systemmentioning
confidence: 99%
“…From the controller point of view, different control strategies are used [5,28,32,46], such as classical techniques as PID algorithm or more advanced strategy such as fuzzy logic controller -FLC. In reference [45], whose aim is to design a low cost two-axis solar tracker for obtaining a high precision positioning of the panel, the control-board is able to support different control strategy, PID and FLC; using the error signal, the tracking capacities of the proposed approaches are tested on an experimental prototype. In reference [12], the implementation of a fuzzy logic neural controller (FNLC) in photovoltaic systems has been studied; this controller, which is an evolution of the fuzzy control concept, allows the system to learn control rules.…”
Section: Issn: 2668-0416mentioning
confidence: 99%